2021
DOI: 10.1161/atvbaha.120.314378
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Therapy–Associated Thrombosis

Abstract: Patients with cancer have an increased risk of both arterial and venous thrombotic events compared with the general population. Both the site and stage of cancer are known to contribute to the increased risk of thrombotic events. In addition, several treatment-related factors enhance the risk of thrombosis, including hospitalization, surgery, central venous catheters, radiation, and anticancer agents. Chemotherapy serves as a mainstay treatment for a broad range of malignancies. Chemotherapeutic agents typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 167 publications
1
71
0
3
Order By: Relevance
“…indirectly activate platelets (Grover et al, 2021). All of these mechanisms may promote thrombosis under malignancies.…”
Section: Hypercoagulable Statementioning
confidence: 99%
See 1 more Smart Citation
“…indirectly activate platelets (Grover et al, 2021). All of these mechanisms may promote thrombosis under malignancies.…”
Section: Hypercoagulable Statementioning
confidence: 99%
“…Alternatively, these drugs may decrease anticoagulants and increase procoagulants, hence tipping the balance towards coagulation. Finally, the anticancer drugs may directly or indirectly activate platelets ( Grover et al, 2021 ). All of these mechanisms may promote thrombosis under malignancies.…”
Section: Common Pathogenic Mechanisms Underlying Thrombosismentioning
confidence: 99%
“…Observational data suggest that some anti-cancer therapies are associated with increased risk for thrombotic events in the venous and arterial vasculature including deep vein thrombosis (DVT), pulmonary embolism (PE), and arterial thrombosis (AT) as recently summarized by Grover et al ( 3 ). Indeed, Weiss et al reported that 5% of stage II breast cancer patients (22/443) with 2 years of post-mastectomy chemotherapy developed venous thrombosis without signs of metastasis ( 4 ).…”
Section: Anthracyclines and Thrombosismentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) represents the most frequent histological form of tumor of the oral cavity and arises in the context of chronic exposure to tobacco and alcohol [ 3 ]. Patients with OSCC receive surgical procedures and medical treatments that put them at risk of thrombosis and hemorrhage [ 4 , 5 , 6 ], but they are usually considered to be at low risk of systemic thrombosis [ 7 , 8 ]. Understanding the biological basis for patient susceptibility to this large spectrum of complications requires fundamental studies on tumor physiology.…”
Section: Introductionmentioning
confidence: 99%